The Role of the Administrative Court in Protecting Citizens' Rights from Harmful Administrative Actions - Kau, Paramita (Estudiante Law Journal, 2025)
The State Administrative Court (PTUN) plays a crucial role in ensuring legal certainty for citizens in administrative disputes. This article examines its role within Indonesia’s legal system and how PTUN ensures that government administrative actions remain within the bounds of applicable laws. This study employs a normative legal research method with a literature review approach. The findings indicate that PTUN functions as a mechanism to oversee administrative decisions and actions that may be detrimental to citizens. Through transparent and accountable legal procedures, PTUN ensures that government decisions are made in accordance with the law, are not arbitrary, and provide protection for the rights of individuals and legal entities. PTUN also contributes to building a fairer, more transparent, and accountable government by upholding the principles of the rule of law and good governance. With PTUN in place, the public has a clear legal avenue to challenge harmful administrative decisions, thereby strengthening legal certainty and social justice in governance